Redefining obesity in the Indonesian population: the critical role of waist-to-height ratio in screening for diabetes mellitus and hypertension - Sartika, Ratu Ayu Dewi; Sigit, Fathimah Sulistyowati; Mohd Shukri, Nurul Husna; Purwanto, Edy; Yunita, Jasrida; Lubis, Pika Novriani (John Wiley and Sons, 2025)
Objectives: Waist-to-height ratio (WHtR) is an alternative index to evaluate metabolic health and predict the risk of estimating the impact of adiposity on cardiometabolic diseases. Despite the significance, the diagnostic performance of WHtR has not been extensively investigated in large epidemiological studies in Indonesia. Therefore, this study aimed to investigate anthropometric indexes (body mass index [BMI], waist circumference [WC], waist-to-hip ratio [WHR], and WHtR) with the best clinically accurate and diagnostic performance in detecting the prevalence of diabetes mellitus (DM) and hypertension (HTN) in the Indonesian population.